Altered Signaling Pathways Revealed by Comprehensive Genomic Profiling in Patients With Unknown Primary Tumors - Yang, Zhen; Cui, Wei; Yu, Ruoying; Dong, Xinhua; Zhao, Jian; Dai, Lu; Ou, Qiuxiang; Bao, Hua; Wu, Xue; Wu, Chuanxin; Lai, Jinhuo (Frontiers in Oncology, 2022)
Purpose: Carcinoma of unknown primary (CUP) is a clinically aggressive disorder with early tumor dissemination. Identifying molecular traits of CUP can be beneficial not only for a better therapeutic approach but also potentially valuable for patients with general metastatic dissemination. Patients and Methods: We retrospectively investigated a total of 35 unique CUP cases. Tumor tissue samples were available in 26 patients and plasma samples were available in 22 patients. Targeted sequencing was performed with a panel of 416 pan cancer-related genes. Results: Genomic landscape of the CUP cohort showed that TP53 mutation was the most frequently observed mutation while MYC amplification was the most common CNV. Aberrant TP53, RTK-RAS, and PI3K signaling pathways were also prevalent, identified in more than half of the cases with tumor tissue. Around 58% of the CUP cases harbored homologous recombinant repair(HRR) pathway gene alterations. Tumor mutational load of CUP patients with altered HRR pathway displayed a significantly increase than patients with intact HRR. Clinically actionable mutations were identified in eight patients, which may benefit from targeted therapies. Eight patients were treated with platinum-based chemotherapy, showing different responses, HRR, and LOH status. Conclusion: Collectively, our data have provided much-need insights into the treatment options for patients diagnosed of with CUP in the era of precision medicine.